دور الرقابة الداخلية في مواجهة مخاطر التحول الرقمي: دراسة تطبيقية على قطاع الأعمال بالبيئة السعودية - محمد، أميرة يسري عبدالفتاح (المجلة العلمية للدراسات والبحوث المالية والتجارية: علمية محكمة., 2025)
تهدف هذه الدراسة إلى تحديد دور الرقابة الداخلية في الحد من المخاطر التي تواجه منظمات الأعمال أثناء عملية التحول الرقمي، حيث اتجهت العديد من المنظمات في ظل التسارع التكنولوجي الحالي إلى تبني الأساليب والتقنيات الرقمية من أجل مواكبة التطور السريع في بيئة الأعمال الحديثة، وعلى الرغم من المزايا المتعددة الناتجة عن التحول الرقمي، إلا أن هناك العديد من المخاطر الناشئة عنه، والإجراءات التي تستخدمها المنظمات للتعامل مع هذه المخاطر يكون لها دورا رئيسيا في نجاح أو فشل عملية التحول الرقمي، حيث يجب توفير الرقابة الفعالة للاستفادة من مزايا التقنيات الرقمية المستخدمة، نظرا لأن مخاطر التحول الرقمي قد تؤثر بشكل كبير على دقة البيانات والتقارير المالية للمنظمة، وقد يؤدي عدم التعامل مع هذه المخاطر بآليات محددة بدقة وغياب الرقابة الداخلية الفعالة إلى عدم القدرة على حماية أصول المنظمة وممتلكاتها، وفقدان الثقة في المنظمة والمعلومات الصادرة عنها، ومن خلال هذه الدراسة تم تحديد أهم أنواع المخاطر التي تواجه عملية التحول الرقمي للمنظمات، بالإضافة إلى اقتراح عدد من الإجراءات التي يمكن أن تساهم في دعم دور الرقابة الداخلية في مواجهة هذه المخاطر، وقد اختبرت الدراسة آراء عينة مكونة من الأكاديميين والمراجعين وغيرهم من المهنيين المتخصصين في المملكة العربية السعودية حول دراسة أثر الرقابة الداخلية في الحد من مخاطر التحول الرقمي، وأشارت نتائج الدراسة إلى وجود دور مؤثر للرقابة الداخلية في الحد من مخاطر التحول الرقمي بمختلف أنواعها، حيث أن النجاح في عملية التحول الرقمي والاستفادة من مزايا تطبيق التقنيات الرقمية الحديثة يرتبط بشكل مباشر بوجود نظام رقابة داخلية مصمم جيدا يؤدي دوره على الوجه المستهدف. This study aims to identify the role of internal control in reducing the risks facing business organizations during the digital transformation process, as many organizations have tended in light of the current technological acceleration to adopt digital methods and techniques in order to keep pace with the rapid development in the modern business environment, and despite the multiple advantages resulting from digital transformation, there are many risks arising from it, and the procedures used by organizations to deal with these risks have a major role in the success of or the failure of the digital transformation process, where effective control must be provided to take advantage of the advantages of the digital technologies used, given that the risks of digital transformation may significantly affect the accuracy of the organization's financial data and reports, and failure to deal with these risks with precisely defined mechanisms and the absence of effective internal control may lead to the inability to protect the organization's assets and property, and loss of confidence in the organization and the information issued by it, and through this study the most important types of risks facing the digital transformation process of organizations were identified, in addition to proposing a number of measures that can contribute to supporting the role of internal control in facing these risks, the study tested the opinions of a sample consisting of academics, auditors and other specialized professionals in the Kingdom of Saudi Arabia on studying the impact of internal control in reducing the risks of digital transformation, and the results of the study indicated that there is an influential role for internal control in reducing the risks of digital transformation of all kinds, as success in the digital transformation process and taking advantage of the advantages of the application of modern digital technologies are directly related to the existence of a well-designed internal control system that performs its role in the targeted manner.